THE INFLUENCE OF INTEGRATED MARKETING COMMUNICATIONS ON THE INDIHOME PRODUCT PURCHASE DECISION PROCESS AT PLASA TELKOM NIAS - Anugerah Zega; Nov Elhan Gea; Yupiter Mendrofa; Serniati Zebua (Jurnal Ilmiah METADATA, 2026)
This study aims to analyze the influence of integrated marketing communications on the purchasing decision-making process for IndiHome products at Plasa Telkom Nias. Integrated marketing communications is a strategy that combines various promotional channels, such as advertising, sales promotions, direct marketing, and social media, to deliver a consistent and compelling message to consumers. This study used a quantitative approach with a survey technique of 57 IndiHome users at Plasa Telkom Nias. Data were collected through a questionnaire and analyzed using validity and reliability tests, simple linear regression, and t-tests. The results of the study indicate that integrated marketing communications significantly influence purchasing decisions for IndiHome products. A significance value of 0.000 (<0.05) and a calculated t-value of 13.561 demonstrate a strong relationship between the two variables. This means that the better the implementation of integrated marketing communications, the higher the consumer's likelihood of purchasing IndiHome products. This research provides a practical contribution for Plasa Telkom Nias in improving marketing communication strategies to more effectively attract customer interest and strengthen consumer loyalty.